Bond-slip behaviour of lightweight aggregate concrete based on virtual crack model with exponential softening characteristics. (22nd August 2022) - Wang, Bin; Zhu, Eryu; Zhang, Zhu; Zhu, Chunqi
Highlights: Establishing analytical model of bond-slip of lightweight aggregate concrete with rebar. The analytical model based on virtual crack model with exponential softening characteristics. The predicted bond-slip relationship is well consistent with the experimental results. Considering the inhomogeneity of bond stress, the expression of bond strength is modified. Abstract: A theoretical analytical model of bond stress-slip between lightweight aggregate concrete and rebar is presented by using the virtual crack model of fracture mechanics to analyze the nonlinear exponential softening characteristics of lightweight aggregate concrete in this paper. Various critical points at different stages are calculated by using simplified expressions. Moreover, a theoretical analytical model for bond-slip mechanism considering the effect of the stirrup is additionally presented. To simulate the relationship of bond stress-slip, a Python program is developed to generate connectors between rebar and concrete corresponding nodes. Furthermore, a three-dimensional finite element model is also developed to consider the impact of radial stress around the rebar. Compared with the bond stress-slip curves of experimental results, the theoretical analytical model of bond-slip behavior effectively reflects the interaction of rebar and lightweight aggregate concrete, and the three-dimensional finite element model demonstrates how cracks within lightweight aggregate concrete expand. At the interface between lightweight aggregate concrete and rebar, the bond stress is not uniformly distributed alongside the bond length. Due to the inhomogeneity of the bond stress, the bond strength calculation equation needs to be modified. Meanwhile, the modified results are well consistent with the bond-slip test.